The Intersection of Islamic Banking and Cryptocurrency: Opportunities and Challenges for Global Finance - Alfi Fuadah (Brilliant International Journal Of Management And Tourism, 2025)
The rapid development of financial technology has introduced cryptocurrency as a transformative innovation within the global financial system, raising fundamental questions regarding its compatibility with value-based financial models, particularly Islamic banking. Grounded in Sharīʿah principles that emphasize ethical finance, risk-sharing, asset-backed transactions, and the prohibition of ribā, gharar, and maysir, Islamic banking faces both opportunities and challenges in responding to the emergence of decentralized digital assets. This study aims to explore how Islamic banking can engage with cryptocurrency while maintaining its normative and ethical foundations, as well as to identify the key constraints that limit institutional adoption within global finance. Employing a qualitative research approach, the study conducts a systematic and interpretive review of scholarly literature, regulatory frameworks, and classical as well as contemporary Sharīʿah sources related to Islamic finance, blockchain technology, and cryptocurrency governance. The analysis reveals that blockchain technology demonstrates substantial alignment with Islamic banking principles through its transparency, traceability, and decentralized verification mechanisms, offering institutional potential in areas such as payments, trade finance, and smart contracts. However, the findings also indicate that cryptocurrency markets are characterized by high volatility, speculative behavior, weak real-sector linkage, and fragmented regulatory oversight, which raise significant ethical, financial, and governance concerns for Islamic banking institutions. Regulatory divergence and inconsistent Sharīʿah interpretations further complicate cross-border implementation and scalability. The study concludes that Islamic banking should adopt a selective and principle-oriented approach to cryptocurrency, distinguishing between permissible technological infrastructure and ethically problematic market practices.